2015
DOI: 10.1080/15476286.2015.1022702
|View full text |Cite
|
Sign up to set email alerts
|

A systematic investigation based on microRNA-mediated gene regulatory network reveals that dysregulation of microRNA-19a/Cyclin D1 axis confers an oncogenic potential and a worse prognosis in human hepatocellular carcinoma

Abstract: MicroRNAs (miRNAs) contribute to a wide variety of human diseases by regulating gene expression, leading to imbalances in gene regulatory networks. To discover novel hepatocellular carcinoma (HCC)-related miRNA-target axes and to elucidate their functions, we here performed a systematic investigation combining biological data acquisition and integration, miRNA-target prediction, network construction, functional assay and clinical validation. As a result, a total of 117 HCC differentially expressed miRNAs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 66 publications
1
28
0
Order By: Relevance
“…We confirmed miR-19a-3p oncogenic role by depressed PIK3IP1 expression, a negative regulator of PI3K. However, there are one study showed miR-19a was downregulated in HCC by analysis biological data acquisition and integration from literature retrieval and inhibit cyclin D1 expression [12]. Different type of HCC cell lines were used in these studies, and maybe was the reason for the discrepancies of those results.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We confirmed miR-19a-3p oncogenic role by depressed PIK3IP1 expression, a negative regulator of PI3K. However, there are one study showed miR-19a was downregulated in HCC by analysis biological data acquisition and integration from literature retrieval and inhibit cyclin D1 expression [12]. Different type of HCC cell lines were used in these studies, and maybe was the reason for the discrepancies of those results.…”
Section: Discussionmentioning
confidence: 57%
“…Some studies have shown that miR-19a-3p is underexpressed in patients with recurrent HCC compared to the nonrecurrence group [11]. It inhibits cell proliferation and promotes more apoptosis in HCC [12].These data indicate its tumor suppressor function but some studies that have been conducted show the opposite effects of miR-19a-3p in HCC. These studies indicate that miR-19a-3p is upregulated in an HCC tumors compared to respective peritumor adjacent tissues [13] and it promotes tumor growth, metastasis, and chemoresistance [14,15].…”
Section: Ivyspringmentioning
confidence: 98%
“…Furthermore, pathophysiological, immune infiltrate promoted inflammation in tumor microenvironment is consistent with potential biological functions of the DNAm markers in the MRscore and DNAmPheno-Age. For example, in addition to four CpGs in the MRscore mapped to genes involved in various cancers (cg23665802 in MIR19A, cg08362785 in MKL1, cg19572487 in RARA, cg05575921 in AHRR) [31][32][33][34][35][36][37][38][39], three CpGs in the MRscore (cg05575921, cg06126421, and cg08362785) were identified to correlate with C-reactive protein, a sensitive indicator of chronic inflammation, in a meta-analysis of EWAS [40]. Six CpGs in the MRscore are strongly related to tobacco smoking [12,41,42], a factor with well-established strong effects on inflammation/immune processes [43,44] and 18 types of cancer such as lung, colorectal, and liver cancer [45], [46].…”
Section: Discussionmentioning
confidence: 99%
“…Network interactions are derived from literature curation or direct user submitted information (http://www.ebi.ac.uk/intact/). Numerous studies have used IntAct molecular network interactions . The molecular network interactions include both physical and functional interactions, and novel molecular targets that are reported in the IntAct database.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have used IntAct molecular network interactions. 35,36 The molecular network interactions include both physical and functional interactions, and novel molecular targets that are reported in the IntAct database.…”
Section: Functional Pathway Analysismentioning
confidence: 99%